2016
DOI: 10.1103/physrevlett.117.247202
|View full text |Cite
|
Sign up to set email alerts
|

Hund’s Rule-Driven Dzyaloshinskii-Moriya Interaction at3d5dInterfaces

Abstract: Using relativistic first-principles calculations, we show that the chemical trend of Dzyaloshinskii−Moriya interaction (DMI) in 3d-5d ultrathin films follows Hund's first rule with a tendency similar to their magnetic moments in either the unsupported 3d monolayers or 3d-5d interfaces. We demonstrate that, besides the spin-orbit coupling (SOC) effect in inversion asymmetric noncollinear magnetic systems, the driving force is the 3d orbital occupation and their spin flip/mixing processes with the spin-orbit act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

25
136
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(169 citation statements)
references
References 50 publications
25
136
2
1
Order By: Relevance
“…Skyrmions are also present in Fe (ultra-)thin-films, e.g., Fe monolayer on Ir(111) [20], Pd/Fe bilayer on Ir(111) [9,10,[30][31][32], 3 monolayers of Fe on Ir(111) [33] and Co ultrathin film Co/Ru(0001) [34]. In that case, magnetic interactions can be tuned by the choice of the magnetic film [35,36], the hybridization with the different substrates [11,35,37,38], or optional overlayers [9]. Pd/Fe/Ir(111) shows isolated skyrmions which can be created and annihilated by the spin-polarized current induced by the spin-polarized scanning tunneling microscope tip [30].…”
Section: Introductionmentioning
confidence: 99%
“…Skyrmions are also present in Fe (ultra-)thin-films, e.g., Fe monolayer on Ir(111) [20], Pd/Fe bilayer on Ir(111) [9,10,[30][31][32], 3 monolayers of Fe on Ir(111) [33] and Co ultrathin film Co/Ru(0001) [34]. In that case, magnetic interactions can be tuned by the choice of the magnetic film [35,36], the hybridization with the different substrates [11,35,37,38], or optional overlayers [9]. Pd/Fe/Ir(111) shows isolated skyrmions which can be created and annihilated by the spin-polarized current induced by the spin-polarized scanning tunneling microscope tip [30].…”
Section: Introductionmentioning
confidence: 99%
“…In such thin film structures, a spatial modulation of interfacial DMI can be realized by a local gating [56], a local modulation of the interface between ferromagnetic layer and heavy metal layer [57][58][59], or a local variation of the heavy metal thickness [60]. For a magnonic crystal with spatially modulated DMI, we establish an effective Schrödinger equation for spin waves and derive spin-wave boundary conditions at the boundary between two regions having different DMI values.…”
Section: Introductionmentioning
confidence: 99%
“…interfaces follows Hund's rule with a similar tendency to their magnetic moments [22]. To verify whether the underlying mechanism of the DMI change in our case is associated from the magnetic moment variation, we plot the corresponding average magnetic moment of each systems in Fig.…”
mentioning
confidence: 82%
“…In order to elucidate the origin of DMI oscillations, in Fig. 1 (c [22] demonstrated that besides the SOC, the electronic occupation of magnetic atom also strongly affects the DMI. In particular, the DMI in 3d/5d…”
mentioning
confidence: 99%